Condensate density of interacting bosons: A functional renormalization group approach - Eichler, Christopher; Hasselmann, Nils; Kopietz, Peter (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2009)
We calculate the temperature-dependent condensate density ρ0 (T) of interacting bosons in three dimensions using the functional renormalization group (FRG). From the numerical solution of suitably truncated FRG flow equations for the irreducible vertices we obtain ρ0 (T) for arbitrary temperatures. We carefully extrapolate our numerical results to the critical point and determine the order parameter exponent β 0.32 in reasonable agreement with the expected value 0.345 associated with the XY -universality class. We also calculate the condensate density in two dimensions at zero temperature using a truncation of the FRG flow equations based on the derivative expansion including cubic and quartic terms in the expansion of the effective potential in powers of the density. As compared with the widely used quadratic approximation for the effective potential, the coupling constants associated with the cubic and quartic terms lead to small corrections of the condensate density. © 2009 The American Physical Society.
Created from Fastlane, Scopus look-up